Pengaruh Financial Technology dan Literasi Keuangan terhadap Keberlangsungan UMKM di Kecamatan Medan Sunggal (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of Financial Technology and Financial Literacy on the Sustainability of UMKM in Medan Sunggal District. The population in this study were all UMKM actors in Medan Sunggal District. The sampling used in this study used a purposive sampling technique which was carried out by selecting UMKM in the Culinary sector of Medan Sunggal District. The type of data used is multiple linear regression using SPSS. The results of this study indicate that Financial Technology and Financial Literacy have a simultaneous effect on the Sustainability of UMKM